2020
DOI: 10.1186/s40001-020-00411-8
|View full text |Cite
|
Sign up to set email alerts
|

Total arthroplasty with Ivory® prosthesis versus resection–suspension arthroplasty: a retrospective cohort study on 82 carpometacarpal-I osteoarthritis patients over 4 years

Abstract: Background: To elucidate the performance of carpometacarpal-I joint prostheses in comparison with the current gold standard treatment, resection-suspension arthroplasty (RA), we conducted a study comparing outcomes of the Ivory prosthesis to those of a cohort of patients receiving RA.Methods: Initially, we had enrolled 34 prosthesis patients and 48 RA patients, of which 5 and 11 were lost to followup. We defined Eaton/Littler stage 3 osteoarthritis, no previous surgery, no concomitant arthrosis, no rheumatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Several studies have been published comparing total joint arthroplasty with trapeziectomy, but only reporting short-term results [1][2][3][4][5]. Jager et al described higher satisfaction, mobility, strength, pain reduction and functional scores in favor of the MAIA® total joint prosthesis [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been published comparing total joint arthroplasty with trapeziectomy, but only reporting short-term results [1][2][3][4][5]. Jager et al described higher satisfaction, mobility, strength, pain reduction and functional scores in favor of the MAIA® total joint prosthesis [1].…”
Section: Discussionmentioning
confidence: 99%
“…The two most widely used surgical procedures for the treatment of osteoarthritis (OA) of the trapeziometacarpal (TMC) joint are the trapeziectomy and TMC joint arthroplasty. In recently published research it is hypothesized that TMC joint arthroplasty is superior compared to trapeziectomy in terms of pain, strength, range of motion (ROM), satisfaction and recovery [1][2][3][4][5]. However, most studies present short-term follow-up and thus long-term data are of interest.…”
Section: Introductionmentioning
confidence: 99%
“…After removal of duplicates and abstract screening, 27 articles were assessed for eligibility by the inclusion criteria. From these 27 studies, 13 were excluded, resulting in 14 eligible studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a flow diagram for the results of the study selection procedure is shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…All five studies [21][22][23][24][25] that compared JR with LRTI alone used the Burton-Pellegrini technique. Four studies adopted RA techniques, of which three [20,26,28] used RSA and one [27] used Lundsborg's RA. The studies utilising TI adopted flexor carpi radialis (FCR) TI [29] and abductor pollicis longus (APL) TI [30].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Non-cemented prostheses provide better results in mid-term follow-up [66,67], high rates of patient satisfaction and 71-92% survival rates in a 10-year follow-up [68,69]. There is a lack of prospective studies directly comparing trapeziectomy with the different prostheses [59], but at present overall prosthetic implants seem to have a higher complication rate and inferior long-term outcomes compared with resection arthroplasty [69,70].…”
Section: Joint Replacement Surgerymentioning
confidence: 99%